Mineral Chemistry of Ulukale Porphyritic Dome and Çağlarca Radial Dykes in the Tunceli Volcanites, Eastern Turkey - Kürüm, Sevcan; Sar, Abdullah; Yurt, Muhammed Yasir (My University, 2025)
This study presents mineral chemistry data the first time as a analytical data for the Ulukale porphyritic dome and the Çağlarca radial dykes located within the Neogene Tunceli volcanic rocks. In petrographic studies, it was determined that the dome and dykes with porphyritic texture were of trachyandesite composition. Plagioclase (oligoclase + andesine), amphibole (hastingsite + magnesiohastingsite and ferroedenite) and biotite (meroxene + phlogopite) found in domes-dykes, and pyroxene (augite and hypersthene) element contents only in dykes indicate that the magma originated from mantle-mantle+crust mixing and was affected by late-stage low-temperature hydrothermal fluids. Pyroxenes indicating low temperature - pressure conditions also indicate an upper crust source. This magma with mantle + crust properties supports crustal thickening and underplating mafic magma formation, which is a result of the compression regime in the Eastern Anatolia region.
Keywords: Tunceli Volcanics; Ulukale-Çağlarca; Porphyritic Dome; Radial Dyke; Mineral Chemistry